2001
DOI: 10.1259/bjr.74.882.740495
|View full text |Cite
|
Sign up to set email alerts
|

Renal arteriography using gadolinium enhanced 3D MR angiography—clinical experience with the technique, its limitations and pitfalls

Abstract: Gadolinium enhanced 3D MR angiography (MRA) is becoming a widely accepted technique for imaging the vascular system. We set out to evaluate its accuracy and reliability in visualization of renal arteries in the clinical setting. Gadolinium enhanced MRA was performed in 15 potential live renal donors and 26 patients suspected of having renal artery stenosis who were referred for digital subtraction angiography (DSA). MRA was performed on a 1.5 T MR scanner in a single breath hold. Images from each study were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 38 publications
1
13
0
4
Order By: Relevance
“…This comes into agreement with a previously reported meta-analysis [27] of all these three modalities, which concluded that GD-enhanced MRA and CTA could be the preferred methods applied in patients referred for the evaluation of renovascular hypertension. The study herein presented followed the careful selection of all patients included with the same criteria and recruitment methods.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This comes into agreement with a previously reported meta-analysis [27] of all these three modalities, which concluded that GD-enhanced MRA and CTA could be the preferred methods applied in patients referred for the evaluation of renovascular hypertension. The study herein presented followed the careful selection of all patients included with the same criteria and recruitment methods.…”
Section: Discussionsupporting
confidence: 91%
“…[19][20][21][22] Contrast-enhanced MRA has been proposed as a reliable alternative to DSA in the detection of renal artery pathology, with reported sensitivity >96% and specificity >92%. [26][27][28][29] The limitations of this method include poor arterial phase timing, inability of the patients to maintain breath-hold, and small imaging volume. Advantages are that the method is noninvasive, there is no radiation, and no allergic reactions have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively long imaging times, impaired image quality due to technical problems and respiratory motion have prevented their widespread use. With the improvement of the MR hardware and software, the breath-hold contrast-enhanced (CE) fast 3D TOF sequence has become a useful technique in assessing the renal arteries [18,19,20,21,22,23,24,25]. …”
Section: Discussionmentioning
confidence: 99%
“…No entanto, inúmeros trabalhos estão apontando o aumento da sensibilidade e da especificidade da angio-RM, principalmente após o surgimento de novas técnicas, mais rápi-das e com melhores resoluções, o que faz deste exame um método completo, visto não ser invasivo, não utilizar radiações ionizantes, não utilizar contraste nefrotóxico e ter índices de complicações insignificantes quando comparado com a angiografia digital (7)(8)(9)(10)(11)14) .…”
Section: Considerações Finaisunclassified